Improving Social Science Learning Outcomes through the Application of Problem Solving Learning Methods - Samriah, Sitti (International Journal of Management and Education in Human Development, 2022)
The purpose of this study is To find out the social studies learning outcomes of class IX.3 students of SMP Negeri 18 Kendari through the application of Problem Solving. Obtain evidence that the application of Problem Solving can improve social studies learning outcomes for grade IX.3 students of SMP Negeri 18 Kendari. Data analysis techniques used in this study are: Data reduction is a simplification process carried out by selecting, focusing, and abstracting raw data into meaningful information. Data exposure is the process of presenting data more simply in the form of narrative presentations, and tabular representations including in matrix formats, graphics, and so on. The inference is the process of taking the essence of the organized data presented in the form of short sentence statements and or formulas but containing a broad understanding. The result of this study showed that Efforts to improve social studies learning outcomes in class IX.3 students of SMP Negeri 18 Kendari can be pursued using problem-solving methods by combining lecture and question and answer methods. The problem-solving method can be carried out with the following steps: there is a clear problem to be solved, looking for data or information that can be used to solve the problem, setting a temporary answer to the problem, testing the correctness of the temporary answer, and drawing conclusions. Cycle I at the beginning of the lesson was preceded by the lecture method, then continued with the problem-solving method. The second cycle used the problem-solving method which was then clarified by the question and answer method. And cycle III combines the two, which are preceded by the lecture method and then clarified by the question and answer method. The evidence that shows an increase in social studies learning outcomes by using problem-solving methods is the acquisition of an average score that increases in each cycle. In the first cycle, the average value obtained was 66.77, in the second cycle, it increased to 73.55, and increased again in the third cycle, which obtained an average value of 84.41. In addition to the average value, student activity also increased, including the aspect of asking questions in the first cycle of 14.51%, the second cycle of 16.13%, and the third cycle of 24.32%. Aspects of responding to other students' responses decreased in cycle III. in the first cycle of 19.35%, the second cycle of 24.19%, and the third cycle of 17.74%. The aspect of answering questions in the first cycle is 17.74%, the second cycle is 20.97%, and the third cycle is 75.81%. The aspect of paying attention to the teacher's explanation in the first cycle was 69.35%, the second cycle was 82.26%, and the third cycle was 87.10%. The aspect of group discussion in the first cycle was 61.29%, the second cycle was 79.03%, and the third cycle was 93.55%. Aspects of class discussion in the first cycle are 72.58%, the second cycle is 83.87%, and the third cycle is 95.16%.